Post-Tsunami Shoreline Changes in Parts of Palu Bay - Rahmawati; Iwan Alim Saputra; Rifandi, Rifdan (LPPM Universitas Tadulako, 2024)
This research was conducted in part of Palu Bay which is included in the administrative area of Palu City. The problems in this study are: (1) How is the change of coastline in some parts of Palu Bay? (2) How much area was affected by the Tsunami in parts of Palu Bay? This study aims to: (1) To know the changes of coastline in some parts of Palu Bay. (2) Know the area affected by the Tsunami in part of Palu Bay. This type of research is quantitative descriptive research. The method used to obtain data is by using Geographic Information System (GIS) analysis with overlay techniques. The results showed that there were changes in the coastline in the form of abrasion or loss of land with a total area of 61.53 hectares and additional land (accretion) with a total area of 5.1 hectares. The total area affected by the tsunami in parts of Palu Bay amounted to 622.83 hectares. The sub-districts that experienced the largest tsunami impact were the Tawaeli district with an area of 169.96 hectares, Mantikulore sub-district with an area of 145.55 hectares, the North Palu sub-district with an area of 116.25 hectares, the Ulujadi sub-district with an area of 104.66 hectares, the West Palu sub-district with an area of 58.39 hectares, while East Palu sub-district was the smallest tsunami impacted area with an area of 28.02 hectares.